Sacred Ecology of Sundarbans: An Ethnographic Approach to Exploring Local Ecological Knowledge and Folk Narratives of the Deltaic Sundarbans of Bangladesh - Majumder, Tuli Guha (The Jahangirnagar Review Part-C, 2025)
The study "Sacred Ecology of Sundarbans" utilizes an ethnographic approach to explore traditional wisdom and local folk narratives within the Sundarbans mangrove forest in Bangladesh. It aims to comprehend community perceptions and interactions with the ecosystem, challenging dominant narratives that attribute environmental degradation solely to local populations. This research includes thorough field investigations and interviews conducted across various areas and communities in the Sundarbans to achieve a more comprehensive and accurate understanding of specific folk narratives and their related practices. By examining folktales and oral traditions, the study highlights the coexistence of traditional knowledge with scientific perspectives, offering a more nuanced perspective on the human environment relationship in the region. As climate change and human encroachment threaten the Sundarbans, these narratives play an essential role in fostering a sense of identity and resilience among its residents. Ultimately, the folklore of the Sundarbans goes beyond mere storytelling; it serves as a foundational narrative that reflects the complexities of human existence in harmony with nature's unpredictable forces, advocating shared responsibility for safeguarding both culture and the environment for future generations.